2022
DOI: 10.21203/rs.3.rs-1486167/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scabies affects quality of life in correlation with depression and anxiety

Abstract: Introduction: A small number of studies have shown that scabies causes impairment in the quality of life in adult patients. There was no study evaluated the depression and anxiety and their relationships between life quality in patients with scabies. The aims of this study are to assess the impact of scabies on adult patients’ quality of life and evaluate the relationship between depression and anxiety levels and impairment in life quality. Methods: This cross-sectional study included adult patients diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…The mean DLQI score of our study population was 13.16±7.638. This value was in concordance with the previous studies of DLQI in scabies, which reported mean DLQI values of between 10.09 and 14.95±4.5 [ 1 , 17 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The mean DLQI score of our study population was 13.16±7.638. This value was in concordance with the previous studies of DLQI in scabies, which reported mean DLQI values of between 10.09 and 14.95±4.5 [ 1 , 17 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, in one study, DLQI in 72.2% of patients was moderate-to-extremely affected. DLQI was ‘affected severely’ in 41.3% (n=38) of our patients, similar to most of the previous studies [ 1 , 17 ]. A mild effect was reported only in one study performed in rural areas, and the authors concluded that this may be attributable to the fact that the QoL is so poor that people do not consider scabies as a problem at all [ 32 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations